Complete stories and poems of Edgar Allan Poe. - Poe, Edgar Allan (Doubleday, 1984)
Presents a collection of Edgar Allan Poe's lyrical poems and stories of mystery, humor, satire, and fantasy. Includes a biographical sketch of the author.